2012
DOI: 10.1590/s1516-635x2012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ph and temperature on the activity of phytase products used in broiler nutrition

Abstract: The activity of three commercial microbial phytase (Aspergillus oryzae, A. niger, and Saccharomyces cerevisae) products used in broiler nutrition was determined at different pH (2.0 to 9.0) and temperature (20 to 90°C) values. Enzymatic activity was determined according to the reaction of the phytase with its substrate (sodium phytate), in four replicates, and was expressed in units of phytase activity (FTU). A. oryzae phytase exhibited optimal activity at pH 4.0 and 40°C, but its absolute activity was the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…RC04 (ANOVA, F (4, 20) = 893.7, P < 10 −15 ). Temperature plays a crucial role in influencing the activity of phytases [ 26 ]; the enzyme phytase releases P from phytate. Figure 2 shows that the P concentration increased with increasing temperature up to 30 °C, then decreased at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…RC04 (ANOVA, F (4, 20) = 893.7, P < 10 −15 ). Temperature plays a crucial role in influencing the activity of phytases [ 26 ]; the enzyme phytase releases P from phytate. Figure 2 shows that the P concentration increased with increasing temperature up to 30 °C, then decreased at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…For phytase enzyme, the optimum working temperature is around 40–45 °C [ 29 ]. As the temperature continues to rise above the optimum, the activity and the rate of the reaction decrease abruptly due to the denaturation of enzyme structure.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, heat stability of phytase was observed at 50–100 °C in phytase derived from diverse microbial sources [ 28 , 33 , 34 , 35 , 36 , 37 , 38 ]. The activity of commercially derived microbial phytase from Aspergillus niger and Saccharomyces cerevisiae was the highest at 45 °C and between 50 °C and 60 °C, respectively [ 39 ]. These results suggested that the thermostability of phytase from the rice was similar to that of microorganisms.…”
Section: Discussionmentioning
confidence: 99%